Domain-Linked and Domain-Specific Competence: a Validation Study of a Two-Dimensional Model of Economic Vocational Competence in Germany - Beifang Ma; Maximilian Krötz; Esther Winther (Vocations and Learning, 2024)
Modeling vocational competence is increasingly crucial for monitoring and enhancing the quality of Vocational Educational Training (VET), particularly in the context of ongoing international comparative studies known as "large-scale assessments" of vocational education and training. This study endeavors to provide well-structured and guideline-compliant empirical evidence for the validation of the two-dimensional construct of economic vocational competence, advancing beyond the current state of research. A sample of 1438 first-year apprentices from two federal states in Germany participated as test-takers. The authentic assessment framework comprised 24 items, assessing two dimensions of vocational competence: domain-linked competence and domain-specific competence in the business/commercial domain. Measurement invariance was assessed across (1) federal states and (2) versions of test booklets, and the Multidimensional Random Coefficient Multinomial Logit model was employed to examine the quality of the two-dimensional vocational competence construct. The results supported the validity of the structure, highlighting the differentiation between domain-linked competence and domain-specific competence. This provides a more substantively accurate representation of trainees' vocational competence compared to a unidimensional model.
Keywords: 370; Vocational Competence; Construct Modeling; Multidimensional Model; Domain-Linked Competence; Domain-Specific Competence